Identification of Internal and External Factors as Basic for Business Strategic of Rasa Gadung Cassava Chips Smes in Pemalang Regency - Sawitania Christiany Dwi Utami Boru Situmorang; Irene Kartika Eka Wijayanti (Indonesian Journal of Food Technology, 2022)
Cassava is the third most popular stapple food crop after rice and corn in Indonesia. One of the advantages of cassava that makes this commodity much in demand by national farmers is its ability to produce a variety of downstreaming products, one of which is cassava chips. Rasa Gadung Cassava Chips’ SMEs is one of the cassava processing industry units located in Pemalang Regency so that cassava processing training is always used as the second priority agenda in the local government working plan. However, Rasa Gadung Cassava Chips’ SMEs is not able to keep up with existing developments and is underdeveloped. Even so, this SMEs is still standing in the midst of a pandemic. Therefore, the purpose of this study was to identify the internal and external factors owned by the Rasa Gadung Cassava Chips’ SMEs. This research was analyzed with a descriptive qualitative method. The selection of respondents was carried out purposively using the judgmental sampling method. The data used are data on internal factors (strengths and weaknesses) and data on external factors (opportunities and challenges) for the last 10 (ten) years. The result showed that Rasa Gadung Cassava Chips’ SMEs have 11 (eleven) internal factors and 14 (fourteen) external factors that can be managed in future research using the IFAS-EFAS matrix.